Determination Of Multi Drug Resistance (MDR) Pseudomonas Aeruginosa Isolated From Clinical Sources (Journal of the College of Basic Education, 2024)
The current study included the isolation and identification of Pseudomonas aeruginosa from different clinical sources, as (51) isolates were obtained from (143) samples collected from several hospitals in the city of Baghdad during September 2023 to December 2023. The antibiotic susceptibility test was done for all isolates using eleven antibiotics. After conducting the sensitivity test, the isolates showed resistance to all the antibiotics used in varying proportions, the highest ratio was to Doxycycline which is 90%, followed by Cefepime, Tetracycline, and Ceftazidime which are ranged between (83%, 75%, and 65%), respectively. While ciprofloxacin, gentamacin, and aztreonam showed the lowest rates of resistance, ranging between (18%, 20%, and 22%), respectively. This study was designed to identify multi-antibiotic resistant P. aeruginosa isolates and test their ability to produce biofilm. It was found that out of 51 clinical isolates of P. aeruginosa bacteria, 26 isolates were multi-resistant to antibiotics, among them, 23 were biofilm producers, while 3 isolates were non-biofilm producers.